Muslims in Burundi Discretion and Neutrality - Luffin, Xavier (ISIM Newsletter, 1999)
On the governor of Ujiji, Mohammed Bin Khalfan (called Rumaliza in Kirundi, ‘the one who takes everything’), decided to extend his power to the North, aiming to reach more ivory and slaves. Bin Khalfan was a member of the Barwani’s, a famous Omani family that had settled in East Africa.
Keywords: Relations -- Oman -- Afrique de l'Est

Parenté, migrations, alliances: les réseaux omani en Afrique orientale et centrale - Le Cour Grandmaison, Colette (Les swahili entre Afrique et Arabie, 1991)
Departing from precise historical and geographical examples, the author tries to explain the simultaneous or successive articulations between the relationship networks, the alliances and the commercial networks of the sections of the Omani al-Ḥārithī tribe in East and Central Africa. The al-Ḥarithī tribe has some 10.000 members and is composed of 31 sections among which five beduin sections (a list on p. 177). The tribe is characterized by an extreme mobility in space and in time, but despite massive emigration at certain times the tribal structures, apparently, have remained stable.
Keywords: Relations -- Oman -- Afrique de l'Est

al-Madkhal ilà ‘l-Islām fī Ifrīqiya, maʿa Dirāsa li’l-Dawr al-ʿUmānī - Qarqash, Muḥammad (Maṭb. Basma, 1995)
Keywords: Relations -- Oman -- Afrique de l'Est